Differentiated Citizenship and Contextualized Morality - Mitnick, Eric J. (Ethical theory and moral practice, 2004)
Political theorists, increasingly, are realizing the virtues of contextuality to conceptual analysis. Just as theory may provide useful standards for the assessment of political practices, so may application of theoretical constructs within particular contexts provide a critical corrective to theory. This essay relates work undertaken within sociolegal studies applying a constitutive methodology to such efforts to contextualize political theorizing. The essay describes how the emphasis placed by constitutive theory on locality and meaning entails a contextual analysis. The essay then demonstrates how a constitutive and contextual approach can enhance our understanding of the moral issues surrounding differentiated citizenship policy. While the most obvious cost associated with differentiated citizenship policy is a loss in formal equality, a contextual assessment demonstrates the prospect of an even deeper, though ultimately contingent, moral loss in self-invention.